High pressure treated Bacillus subtilis spores — Structural analysis by means of synchrotron and laboratory based soft X-ray microscopy. (May 2015) - Seim, Christian; Reineke, Kai; Werner, Stephan; Dehlinger, Aurélie; Legall, Herbert; Stiel, Holger; Kanngießer, Birgit
Abstract: Measurements were carried out on high pressure treated (HPT) bacterial endospores of the Bacillus subtilis strain PS832 by means of laboratory (LTXM) and synchrotron based transmission soft X-ray microscopy (SynchTXM). Using LTXM at 500 eV HPT spores could be identified by a higher transparency, due to dipicolinic acid (DPA) release from the spore's core, and their shriveled appearance caused by air-drying. Dormant spores were investigated at different photon energies at SynchTXM. Inner structures were visualized and it was shown that at a photon energy of 280 eV the micrographs yielded bigger absorption differences, and thus better contrast between the core/coat and the peptidoglycan-rich cortex. Tilt series of dormant and HPT spores were reconstructed. Virtual sections revealed the dormant spores' core, cortex and coat without the need to physically slice the sample. It was also possible to visualize the inside of the HPT spores, which proved to be void of DPA. Industrial relevance: Isostatic high pressure processing (HPP) is often regarded as the major recent technological innovation in food preservation. However, this technology is only applied in large scale for pasteurization and not for sterilization, which is largely due to the unknown inactivation mechanisms of highly resistant bacterial endospores. The structural analysis of high pressure treated endospores by X-ray microscopy could be used to study the progress of spore germination and inactivation under pressure and may add to the information already gathered in previous studies such as (Reineke et al., 2013) to establish the high pressure thermal sterilization at industrial scale. This technology in combination with different extrinsic factors like chemical or thermal preservation may open up new possibilities for a multi-target spore inactivation strategy for food sterilization. Highlights: Laboratory transmission soft X-ray microscopy investigations of (high pressure treated) B.subtilis bacterial endospores Synchrotron transmission X-ray microscopy 3D reconstructions of (high pressure treated) B.subtilis bacterial endospores Synchrotron transmission X-ray microscopy measurements below and above the absorption edge of carbon (K edge at 282 eV) Transmission X-ray microscopy is less invasive than previously presented methods to structurally analyze bacterial endospores